Brief review: climate change and its impact on mango pests and diseases - Lee Yit Leng; Osumanu Haruna Ahmed; Mohamadu Boyie Jalloh; Azwan Awang; Norawanis Abdul Razak; Adiza Alhassan Musah; Syahirah Shahlehi (ResearchGate, 2023)
Climate change is negatively impacting the agricultural sector. This review focuses on the effects of climate change on mango pests and diseases, the unknown aspects of this problem, and possible mitigation measures. In addition, mango is susceptible to several pests and diseases infestation at all its stage of life. The major abiotic factors associated with climate change that affect mango pests and diseases include changes in precipitation, wind variability, increased temperature, increases in atmospheric CO2, and changes in light intensity. These factors affect mango pests and diseases in various dimensions in one way or another, including increased activity, growth, development, reproduction, distribution, and migration. These abiotic factors also influence plant growth, development, and reproduction. These interacting factors are complex, and further studies are needed to obtain relevant data to understand the relationships between these factors and pests occurrence. Developing predictive models from these data and intercropping with aromatic plants will be useful for strategies to mitigate the devastating effects of pests and diseases occurrence on mango crops and food security